Studi Kasus : Upaya Penyelesaian Surat Permintaan Penjelasan Data dan/atau Keterangan (SP2DK) Atas Kelalaian Penerbitan Faktur Pajak Pertambahan Nilai (PPN) - Pertiwi, Ajeng Rachma; Andini, Amelia Pratista; Pangesti, Nitami Galih; Firmandani , Wahyu (Jurnal Manajemen dan Organisasi, 2024)
PT M is a developer engaged in property and has been confirmed as a Taxable Entrepreneur (PKP) in 2017. In 2023 PT M received a Request for Explanation of Data and/or Information (SP2DK) from the Tax Service Office (KPP) for indications that tax invoices for the period January - December 2020 had not been reported. This research aims to find out the causes and procedures for resolving the SP2DK obtained by PT M. The method used in this research is a case study with document archive techniques and interviews. This research in testing the validity of qualitative data processing uses the data triangulation method. From the results of this study, it is known that the cause of the issuance of SP2DK is because PT M has not reported tax invoices in the Tax Return (SPT) for the Value Added Tax (VAT) period that has been approved in the e-invoice application. PT M argued that there were concerns about the deadline for uploading tax invoices after the issuance of Director General of Taxes Regulation Number PER 03/PJ/2022. On December 18, 2023, PT M responded to SP2DK in writing to KPP. The resolution of the problem is that PT M has corrected the VAT periodic tax return for unreported tax invoices with a nominal result of underpayment for the January - December 2020 period of Rp 240,776,389.